PROFESSIONAL FOOTBALL LEAGUE OF THE REPUBLIC OF KOREA: FEATURES AND BRAND POTENTIAL - Fadeeva A.V.; Dorskiy A.A.; Gromova T.M.; Nikonov S.B.; Puyu A.S. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to determine the national characteristics of the professional football league of the Republic of Korea (RK) and to assess the brand potential of this sport for the country. Methods and structure of the study. The research method of the case study with a single result (single-outcome study) was taken as the main tool of the methodological base to determine the specifics of the experience of the Republic of Korea. Results and conclusions. The authors analyzed the national features of the functioning of the K League 1 (Korean Professional Football League), which takes place annually from March to November, where 12 regional teams participate. The article gives a brief description of the clubs and analyzes their brand potential as a factor influencing the prestige of the state in the field of politics and international sports. The effectiveness of the training system for athletes of the major leagues was assessed based on the results of the 2022 FIFA World Cup held in Qatar.